2021
DOI: 10.3390/polym13244351
|View full text |Cite
|
Sign up to set email alerts
|

Composite Polymers from Leather Waste to Produce Smart Fertilizers

Abstract: The leather industry is facing important environmental issues related to waste disposal. The waste generated during the tanning process is an important resource of protein (mainly collagen) which can be extracted and reused in different applications (e.g., medical, agricultural, leather industry). On the other side, the utilization of chemical fertilizers must be decreased because of the negative effects associated to an extensive use of conventional chemical fertilizers. This review presents current research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 115 publications
0
13
0
1
Order By: Relevance
“…A new agritech revolution is springing up, driven by the developments in information technology, robotics, genetics, plant probiotics, and the evolution of controlled-release systems . In the specific case of CRFs, an important achievement is focused on: low-solubility fertilizers, coated fertilizers, superabsorbent biobased polymers (SABs), and nanofertilizers (specifically, nanomaterials used as macronutrient carriers). , SABs have attracted considerable attention due to their three-dimensional cross-linked polymer networks that have a great potential to absorb and retain large amounts of water, while reducing irrigation times. , The recent development of nanofertilizers with high surface areas and sorption capacity for nutrients improves the NUE in plants by a faster response through different adsorption routes (i.e., seed treatment, soil amendment, and foliar spray) (Figure ). ,, Different studies have demonstrated that nanofertilizers are an emerging CRF alternative to improve NUE. , For instance, in both soil and water, hybrid nanofertilizers increased the NUE in A. esculentus , as compared to a conventional fertilizer .…”
Section: Future Perspectives In the Agriculture Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…A new agritech revolution is springing up, driven by the developments in information technology, robotics, genetics, plant probiotics, and the evolution of controlled-release systems . In the specific case of CRFs, an important achievement is focused on: low-solubility fertilizers, coated fertilizers, superabsorbent biobased polymers (SABs), and nanofertilizers (specifically, nanomaterials used as macronutrient carriers). , SABs have attracted considerable attention due to their three-dimensional cross-linked polymer networks that have a great potential to absorb and retain large amounts of water, while reducing irrigation times. , The recent development of nanofertilizers with high surface areas and sorption capacity for nutrients improves the NUE in plants by a faster response through different adsorption routes (i.e., seed treatment, soil amendment, and foliar spray) (Figure ). ,, Different studies have demonstrated that nanofertilizers are an emerging CRF alternative to improve NUE. , For instance, in both soil and water, hybrid nanofertilizers increased the NUE in A. esculentus , as compared to a conventional fertilizer .…”
Section: Future Perspectives In the Agriculture Industrymentioning
confidence: 99%
“…211,213 SABs have attracted considerable attention due to their three-dimensional cross-linked polymer networks that have a great potential to absorb and retain large amounts of water, while reducing irrigation times. 159,160 The recent development of nanofertilizers with high surface areas and sorption capacity for nutrients improves the NUE in plants by a faster response through different adsorption routes (i.e., seed treatment, soil amendment, and foliar spray) (Figure 5). 161,162,214 Different studies have demonstrated that nanofertilizers are an emerging CRF alternative to improve NUE.…”
Section: Future Perspectives In the Agriculture Industrymentioning
confidence: 99%
“…Some research has focused on the use of leather waste in wood-based composites, highlighting its potential as a reinforcing material. These review articles [14,15] present current research trends and prospects for the use of leather waste to produce composite polymers that are further transformed, for example into smart fertilizers. They produced value-added boards using leather particles and partially liquefied bamboo fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous works [ 21 , 22 , 23 ] reported on the synthesis and physical–chemical characterization of novel collagen-based hydrogels by recycling the protein hide waste from the leather industry in ecological conditions and obtaining advanced collagen-based composites with N, P, and K nutrients encapsulated and functionalized with two synthetic polymers, namely poly-acrylamide and poly(sodium 4-styrenesulfonate-co-glycidyl methacrylate) (P(SSNa-co-GMAx), and two natural compounds, namely starch and dolomite, in order to be used as fertilizers for poor soil amendment. The reason why the last two natural compounds were selected for collagen functionalization was to test their efficacy on improving fertilizer quality by using starch as an organic and dolomite as a mineral amendment, as they are both available in high amounts and as waste to be recycled.…”
Section: Introductionmentioning
confidence: 99%